Diaphragmatic breathing exercises in recovery from fatigue-induced changes in spinal mobility and postural stability: a study protocol - Amiri, Banafsheh; Zemková, Erika (Frontiers in Physiology, 2023)
Prolonged periods of sitting at work can increase trunk muscle fatigue from the continuous contraction of deep trunk muscles. Insufficient activity of these muscles can decrease muscular support to the spine and increases stress on its passive structures. This can lead to reduced spinal mobility and impaired postural stability. It may also stimulate nociceptor activity leading to pain. However, frequently used recovery modalities such as muscle strengthening and stretching exercises can be timeconsuming, impractical, and difficult to implement in the workplace. Diaphragmatic breathing exercises, which increase the activity of the deep trunk muscles by raising intra-abdominal pressure, seem to be a suitable alternative. However, little is known as to what extent diaphragmatic breathing exercises contribute to the reduction of fatigue induced by prolonged sitting. This paper presents a study protocol that aims to investigate the acute effect of diaphragmatic breathing exercises on recovery of fatigue-induced changes in spinal mobility and postural stability in sedentary middle-aged adults at risk of developing non-specific low back pain. Twenty sedentary adults aged between 25-44 years will perform Abt's fatigue protocol, followed by (1) active recovery using diaphragmatic breathing exercises and (2) passive recovery in the form of lying on the bed, respectively. There will be one week of rest in between. Pre-fatigue, post-fatigue, and after the active and passive recovery, spinal mobility, and postural stability will be evaluated using the spinal mouse device and a posturography system, respectively. The electromyography will be used to determine the muscle-fatigue conditions. We hypothesize that active recovery in a form of diaphragmatic breathing exercises would be more effective in restoring spinal mobility, and postural stability followed by the fatigue of back and hamstring muscles compared to passive recovery in sedentary adults. Increasing core and respiratory muscle strength via these exercises could be beneficial for overall mobility and stability of the spine. Reducing compressive stress on the passive structures of the spine may be also beneficial for lowering low back pain. Therefore, we believe that diaphragmatic breathing exercises have the possibility to be incorporated into the workplace and contribute to better back health in sedentary middle-aged adults.